Fitz : [large type] Tom Fitzpatrick : an extraordinary mountain life - Blevins, Winfred (Center Point Large Print, 2024)
"Thomas Fitzpatrick always longed for something more -- to see more, do more, and be more. At just seventeen, he leaves home and sails up the Mississippi River in the winter of 1822. Crossing paths with the famed explorer, William Clark, marks the beginning of his epic adventures as a fur trader, leading him through trials and triumphs that are beyond anything he could have ever hoped for. Fitz's adventures unfold as he travels with a diverse group of companions, seeking the wild wonders of an untamed frontier. From surviving battles and discovering crucial routes through the Rockies to becoming a respected Indian negotiator, his life intersects with numerous iconic figures of his time, including Jim Bridger, Jedediah Smith, and Kit Carson. As Fitz embarks on his long-awaited journey into the rugged landscapes of the American West, he begins to grasp that the life he's yearned for is tantalizingly close. But as he teeters on the brink of exhilarating experiences, the question looms: Will this newfound existence on the edge be his salvation . . . or his ultimate demise?"--